Management of Wolff-Parkinson-White syndrome in a patient with peripartum cardiomyopathy - Snigdha Bendaram; Sherif Elkattawy; Muhammad Atif Masood Noori; Hardik Fichadiya; Sarah Ayad; Parminder Kaur; Raja Pullatt; Fayez Shamoon (Greater Baltimore Medical Center, 2021)
Wolf-Parkinson-White (WPW) syndrome is a congenital heart condition in which the atrioventricular (AV) node is bypassed by an accessory pathway that connects the atria and ventricle directly along with symptoms of syncope or palpitations. WPW syndrome in patients with a history of peripartum cardiomyopathy (pregnancy-related cardiomyopathy) is associated with a high risk of morbidity and mortality secondary to failure of the pump and the conduction system of the heart. Management of these cases deals with arrhythmia and systolic heart failure, which becomes more challenging in pregnant patients as it requires treatment methods that minimize risks to the fetus. We report a case of a young female patient with WPW syndrome and peripartum cardiomyopathy presenting with symptomatic arrhythmias (tachycardia).